Identity in supervision : understanding who works for you and who you work for in higher education - Nasser, Roger, Jr (Identity & practice in higher education-student affairs., 2023)
"This book will discuss the intersection of personal identity, professional identity, and positionality with supervision techniques. The structure of the text will outline historical contexts to supervision, development of models, connection to identity, and impact of position while providing a framework for self-reflection. Various populations including new professionals, middle managers, senior administrators, faculty, and graduate students will connect to the themes of the text. Readers will benefit from self-reflection, review, and understanding. Identity in supervision: Understanding who works for you and who you work for in higher education, will introduce faculty, staff, administrators, and graduate students in higher education to the intersection of identity and positionality to the supervision experience. Specifically, this publication centers on understanding the people behind the positions and how best to support them. The text is constructed in four sections. Section 1: Understanding Supervision in Higher Education contains chapters, which provide an overview of supervision. This overview is essential as later chapters examine specific populations and positions. Section 2: The Impact of Identity on Supervision in Higher Education includes chapters, which ask readers to reflect on how their own identities impact their supervision experience and the experience of their colleagues. Section 3: the Impact of Professional Experience on supervision reviews the specific needs of professionals at different experience levels. Readers will improve their understanding of both those they supervise and their supervisors. Finally, Section 4: The Impact of Functional Area on Supervision contains chapters reviewing the specific needs of professionals in positions in residence life, academic advising, judicial affairs, etc. Supervisors will find this section useful in understanding and supporting these professionals. Each chapter will conclude with two or three reflection questions supporting application. As a result of engaging with this text, readers will be better equipped to understand the impact of identity, experience, and functional area on supervision. They will learn techniques to improve their current practice, reflect on their own needs, and combine ideas from chapters to provide a better experience for all employees"--